The Implementation of Project Based Learning (PjBL) Model Using Local Tourism Video to Improve Students’ Speaking Skill of Tourism Program at SMK - Arismunandar; Ansar; Jusnita , Naniek (PT FORMOSA CENDEKIA GLOBAL, 2024)
The low students’ speaking ability in learning English on tourism concept demands the need for an innovative learning model which is the main problem in this research. The research aims to determine the effectiveness of project based learning (PjBL) model using local tourism videos in improving students' speaking skills. This type of research is a mixed method with qualitative and quantitative analysis design. The data collection techniques used were observation, and students’ speaking tests. The data obtained were analysed descriptively and quantitatively. The results showed that the implementation of the PjBL model assisted by local tourism videos proved effective in improving students' speaking skills with the initial average pre-test value was 57.33 and the average post-test value was 82.85. The normality test value was 0.460 which was distributed normally while the hypothesis value was 0.05, that is mean H0 is rejected and Ha is accepted, thus it can be concluded that there is an improvement on students’ speaking ability at tourism class students through the implementation of the PjBL model using local tourism videos